(untitled) (Research, Society and Development, 2026)
The advancement of Artificial Intelligence (AI) and 3D Printing enables innovations in the treatment of cardiovascular diseases. These technological tools play a fundamental role in producing individualized 3D models and simulating techniques during surgical procedures. The objective of this study is to analyze the role of Artificial Intelligence and 3D Printing in creating personalized therapeutic planning for cardiovascular diseases. This is an Integrative Review, using data from the National Library of Medicine (PubMed) and the Scientific Electronic Library Online (SciELO), covering the years 2019 to 2024. The descriptors applied were: Artificial Intelligence AND Printing Three-Dimensional AND (Cardiovascular Surgical Procedures OR Cardiovascular). These descriptors are aligned with the Health Sciences Descriptors (DeCS). The use of 3D printing and Artificial Intelligence in the cardiovascular field has provided greater precision in diagnoses, surgical planning, and therapeutic personalization. Imaging exams such as Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) are essential for creating three-dimensional models, supported by specific algorithms and software. These technologies benefit cases such as congenital heart diseases, aortic dissections, and valve replacements, for example, by enabling better anatomical visualization, enhancing medical training, and improving communication with the patient. 3D printing and Artificial Intelligence contribute to the personalized treatment of cardiovascular diseases. However, as this is an evolving field, there is still a lack of information and a need for further studies.